2010
DOI: 10.2174/156720510791383796
|View full text |Cite
|
Sign up to set email alerts
|

The Cerebrospinal Fluid Amyloid β42/40 Ratio in the Differentiation of Alzheimers Disease from Non-Alzheimers Dementia

Abstract: The CSF Abeta42/Abeta40 ratio improves differentiation of AD patients from VaD, DLB and non-AD dementia patients, when compared to Abeta42 alone, and is a more easily interpretable alternative to the combination of Abeta42, p-tau and t-tau when differentiating AD from either FTD or non-AD dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(44 citation statements)
references
References 40 publications
1
42
0
Order By: Relevance
“…Aβ40 and Aβ42 were significantly lower in the EV fraction than in the EV-depleted medium fraction and in the parent cell lysates (Figure 1E). Given that the Aβ42/Aβ40 ratio may be a better predictor of AD than the individual concentrations of Aβ40 and Aβ42, we calculated the Aβ42/Aβ40 ratio 31,32 and found that the Aβ42/Aβ40 ratio in EVs was significantly higher than in EV-depleted medium or cell lysate (Figure 1F). …”
Section: Resultsmentioning
confidence: 99%
“…Aβ40 and Aβ42 were significantly lower in the EV fraction than in the EV-depleted medium fraction and in the parent cell lysates (Figure 1E). Given that the Aβ42/Aβ40 ratio may be a better predictor of AD than the individual concentrations of Aβ40 and Aβ42, we calculated the Aβ42/Aβ40 ratio 31,32 and found that the Aβ42/Aβ40 ratio in EVs was significantly higher than in EV-depleted medium or cell lysate (Figure 1F). …”
Section: Resultsmentioning
confidence: 99%
“…While the ratio of Aβ40 to Aβ42 is typically around 5:1 in cerebrospinal fluid of normal individuals (Spies et al, 2010), the insoluble Aβ in AD brain tissue is often predominantly Aβ42 (Gravina et al, 1995). Full structural models for Aβ42 fibrils based on ssNMR data have not yet been published.…”
Section: Molecular Structural Basis For Amyloid Polymorphismmentioning
confidence: 99%
“…This can be expressed as the ratio between sAPPβ and sAPPα (sAPPβ/α) and the ratio between the relative expression of the long Aβ species generated by the amyloidogenic pathway (17-42 aa) in relation to the short Aβ species generated by the non-amyloidogenic pathway (13-16 aa). Furthermore, the ratio between cerebrospinal fluid (CSF) Aβ42 and Aβ40 (Aβ42/40) can be regarded as a marker of the total amyloid load in the brain reflected by amyloid positron emission tomography (PET) [18,19,20]. …”
Section: Introductionmentioning
confidence: 99%